Masa Depan Energi Terbarukan Indonesia: Menelisik Kepentingan Nasional Indonesia dalam Aliansi Belt and Road Initiative Green Development Coalition (BRIGC) - Risma Ayu Septutianingsih; Nisa Khoerunisa (Jurnal Politikom Indonesiana, 2025)
China’s success in international cooperation through its mega project, the Belt and Road Initiative (BRI), was followed by establishing the Belt and Road Initiative Green Development Coalition (BRIGC), which aims to promote green development in several partner countries. To accelerate the transition from conventional to renewable energy, Indonesia joined as a partner in this green development project at the time of BRIGC’s formation by Xi Jinping in 2019. This study aims to understand how Indonesia interprets and implements its national interests within the Belt and Road Initiative Green Development Coalition (BRIGC) as a response to the pursuit of greener and cleaner BRI development. The research uses a qualitative method, with data collected through a literature study. It employs the theory of national interest by Jack Plano and Roy Olton. The findings indicate that Indonesia has national interests in the form of self-preservation and economic well-being that it seeks to achieve through this cooperation, while also striving to balance environmental preservation. However, due to Indonesia's financial limitations, China’s dominance remains evident in several energy projects, as research shows that China holds crucial shares in global mining resources. Keywords: Belt and Road Initiative Green Development Coalition, China, Indonesia, National Interest